FRI0662 Calprotectin s100 a8/a9 in a south african rheumatoid arthritis (RA) cohort. (12th June 2018) - Meyer, P.; Van Rooyen, G.; Anderson, R.; Ally, M.; Winchow, L.; Govind, N.; Tickly, M.; Bang, H.
Abstract : Background: Calprotectins(CLP) S100 A8/A9 are small calcium binding proteins[1] belonging to the group of damage-associated molecular patterns (DAMPs) or alarmins. They play a key role in the inflammatory response in RA. [2, 3]The measurement of CLP S100 A8/A9 in serum may be a useful strategy to optimize management of patients with RA.[4] Objectives: To evaluate serum calprotectin S100 protein (A8 and A8/A9) levels in a South African RA Cohort in relation to disease severity at presentation in comparison with traditional RA-associated autoantibodies. Methods: This was an observational, single-centre study, involving patients attending the Rheumatology Clinic of the Department of Internal Medicine, Chris Hani Baragwanath Academic Hospital (CHBAH) and University of the Witwatersrand, South Africa. The cohort consisted of 128 ethnic black RA DMARD-naïve patients. The study was approved by the local ethics committee and patients gave informed consent to participate. Results: The baseline demographics and clinical data of the cohort are summarized in table 1. Calprotectin S100 A8 demonstrated a statistically significant association with disease severity[(both SDAI (p=0.005) and DAS 28 (p=0.016)] by linear regression analysis. Calprotectin S100A8/A9 also showed significant associations with SDAI (p=0.010) and DAS28 (p=0.022) figure 1. Conclusions: Unlike those of traditional autoantibodies, serum levels of calprotectin correlate strongly with disease severity of RA patients. These findings suggest that calprotectin S100 is a promising biomarker for assessment and monitoring of disease activity in RA. References: 1. Cesaro A, Anceriz N, Plante A, Page N, Tardif MR, Tessier PA. An inflammation loop orchestrated by S100A9 and calprotectin is critical for development of arthritis. PLoS ONE2012;7(9):e45478. 2. Geven EJ, Van Den Bosch MH, Di Ceglie I, Ascone G, Abdollahi-Roodsaz S, Sloetjes AW, et al. S100A8/A9, a potent serum and molecular imaging biomarker for synovial inflammation and joint destruction in seronegative experimental arthritis. Arthritis Res Ther2016;18(1):247. 3. Nielsen UB, Bruhn LV, Ellingsen T, Stengaard-Pedersen K, Hornung N. Calprotectin in patients with chronic rheumatoid arthritis correlates with disease activity and responsiveness to methotrexate. Scand J Clin Lab Invest2017. doi:10.1080/00365513.2017.1413591:1-6 4. Obry A, Lequerre T, Hardouin J, Boyer O, Fardellone P, Philippe P, et al. Identification of S100A9 as biomarker of responsiveness to the methotrexate/etanercept combination in rheumatoid arthritis using a proteomic approach. PLoS ONE2014;9(12):e115800. Disclosure of Interest: None declared